Qualification or invitation ? : an enquiry into the holy communion sacrament in the Methodist church in Zimbabwe until completion. - Maburutse, Cloudious (Midlands State University, 2020)
Holy Communion is at the centre of tug of war taking place between two systems of qualification and invitation in the Methodist Church in Zimbabwe. Currently, the Methodist Church in Zimbabwe is at the cross roads and the situation is putting the organization into a serious dilemma. This study tries to bridge a gap between the two theological phenomena at logger heads by taking recourse to a theological reflection on their biblical validity. In fact the research seeks to furnish essential information about the way in which the Holy Communion Sacrament is supposed to be practiced considering the fact that there are two warring Eucharist traditions which are Holy Communion by Qualification and Holy Communion by Invitation. The purpose of this research is premised on the fact that there is no harmony in the way MCZ is supposed to practice Holy Communion hence each minister practice as they are convinced. According to my research findings literature has revealed that the invitation and qualification systems of administering Holy Communion are both biblically evident. The findings from questionnaires to general church members reveals that qualification is more preferable to most Church members despite the biblical validity of both of them. Interviews of some ministers and key Informants revealed that invitation is more preferable to them probably because they are more informed. I argue that both qualification and Invitation systems of administering Holy Communion have biblical validity, and that they should complement each other. I use qualitative methodology, using data gathering methods like, in-depth and phone call interviews, document analysis (both Church documents and researched works on the Eucharist Tradition), being guided by the phenomenological approach. I also use questionnaires and participant observation, methods of gathering data.